Proposed new design for Aprilia Showroom At 43-A, Jalan Pahang, 53000 Kuala Lumpur / Mohd Shah Rizal Mohd Yusuf - Mohd Yusuf, Mohd Shah Rizal (Faculty of Architecture, Planning and Surveying, 2006)
1.1.1 Design Mission The intended mission is to create a design that: 1. To design an interior space for Chear Motor Sdn. Bhd. super bike showroom at 43-A, Jalan Pahang, 53000 Kuala Lumpur. 2. The design will create a sporty and stylish environment. 3. To portray the right image for Aprilia Showroom intended function, vision, mission and objective principle. 4. The value of technical design in consideration of compliance technical...